Competing Notions of Diversity in Archipelago Tourism: Transport Logistics, Official Rhetoric and Inter-Island Rivalry in the Azores - Godfrey Baldacchino; Eduardo Costa Duarte Ferreira (Island Studies Journal, 2013)
Contending and competing geographies are often implicitly involved in archipelagic spaces. Various small island states and territories with multi-island geographies have flourishing tourism industries that presuppose an archipelagic experience: visitors are encouraged to explore and sample different island constituents of the territory. This strategy taps into different tourism niche markets, improves local value added, and shares tourism revenue beyond key nodes and urban centers. The organization of such an important economic activity however often reflects a ‘one-size-fits-all’, tightly coordinated, frequently contrived process that does not necessarily speak to the cultural and biogeographical forms of diversity that reside in the archipelago. This paper offers the notion of archipelago as a new way of rethinking problems and challenges encountered in island tourism, and then assesses the implications of this conceptualization on the representation of ‘the archipelago’ in the Azores, Portugal, and reviews what this approach means and implies for sustainable tourism policy.